Identification Of The Productive Role Of Coastal Women In The Utilization Of By-Catches Fish In Cirebon District - Novianti, Teni; Nurkhasanah, Devi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
The potential for capture fisheries production in Cirebon waters produces by-catch (bycatch) of 49% - 58.93% and for low-economic bycatch fish that are not absorbed in the market are not properly utilized. Based on these problems, it is necessary to utilize bycatch fish, especially fish that have a low economy around the waters of Cirebon Regency so that their utilization can be optimized in increasing added value and business income. The aim of this research is to identify the productive role of coastal women in the use of HTS fish in Cirebon Regency and to find out the percentage contribution of coastal women's income in improving the economy of fishing families. The research method uses a descriptive method with survey techniques and the sampling method uses a purposive sampling technique with the target object of this research being coastal women in Gebang, Mundu and Gunung Jati Districts, Cirebon Regency who use HTS fish as a productive activity. The potential of HTS fish in Cirebon Regency has been exploited by coastal women, not only selling it fresh but also using it in various processed products to increase added value. Coastal women in utilizing bycatch fish in Cirebon Regency have a productive role in the fisheries sub-sector with an average length of work of around 7-8 hours/day and an average age in the very productive category (31-50 years). Coastal women who use bycatch fish not only have a productive role but also have a potential role in increasing the contribution of family economic income, namely 50.09%.